BARRIERS TO MARKETING OF INFORMATION PROUCTS AND SERVICES IN LIBRARIES - Mahesh, G. (DESIDOC Journal of Library & Information Technology, 2003)
In the present information age, wherein information and knowledge are key to societal development, libraries and information centres are potential source of revenue generation if the resources of the libraries and information centres are marketed. Ever since the concept of marketing was introduced to libraries, certain barriers have prevented the libraries in implementing marketing programmes. This paper attempts to look at the barriers that impede the libraries and information centres from adopting marketing. http://dx.doi.org/10.14429/dbit.22.3.3567